PENERAPAN SISTEM KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PT. TORINI JAYA ABADI - Hartadi Wijaya (CV. Denasya Smart Publisher, 2025)
Every process within a company is inevitably accompanied by potential hazards and risks of workplace accidents for employees. Therefore, a company requires an Occupational Health and Safety (OHS) program to minimize and prevent workplace accidents. This study aims to examine the implementation of Occupational Health and Safety at PT. TORINI JAYA ABADI. The data collection methods used in this research include interviews, observations, and literature studies. Meanwhile, the data analysis technique employed is descriptive analysis. The research object selected is the workforce of PT. TORINI JAYA ABADI. Through the interview method, the researcher interviewed the Head of the Work Unit at PT. TORINI JAYA ABADI regarding the implementation of Occupational Health and Safety within the company. Based on the research findings, it is evident that the implementation of Occupational Health and Safety at PT. TORINI JAYA ABADI is quite good and aligns with the applicable regulations. Based on the results, it is recommended that PT. TORINI JAYA ABADI enhance supervision and issue strict warnings to employees who fail to comply with Occupational Health and Safety policies to ensure more effective implementation.